2015
DOI: 10.1016/j.immuni.2015.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic β-Cells Limit Autoimmune Diabetes via an Immunoregulatory Antimicrobial Peptide Expressed under the Influence of the Gut Microbiota

Abstract: Antimicrobial peptides (AMPs) expressed by epithelial and immune cells are largely described for the defense against invading microorganisms. Recently, their immunomodulatory functions have been highlighted in various contexts. However how AMPs expressed by non-immune cells might influence autoimmune responses in peripheral tissues, such as the pancreas, is unknown. Here, we found that insulin-secreting β-cells produced the cathelicidin related antimicrobial peptide (CRAMP) and that this production was defecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
282
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 251 publications
(295 citation statements)
references
References 53 publications
11
282
0
2
Order By: Relevance
“…These results therefore suggest a dichotomy in tTreg and pTreg function: tTreg, presumably specific for self-antigens, would protect the organism from autoimmune disease, whereas pTreg, presumably specific for non-self-antigens found in the mucosa, would avoid chronic inflammation. However, pTreg are also known to inhibit autoimmune (type 1) diabetes in mice, showing that this separation of functions of tTreg versus pTreg, if largely confirmed, is not absolute [15] .…”
Section: Functions Of Ttreg and Ptregmentioning
confidence: 99%
“…These results therefore suggest a dichotomy in tTreg and pTreg function: tTreg, presumably specific for self-antigens, would protect the organism from autoimmune disease, whereas pTreg, presumably specific for non-self-antigens found in the mucosa, would avoid chronic inflammation. However, pTreg are also known to inhibit autoimmune (type 1) diabetes in mice, showing that this separation of functions of tTreg versus pTreg, if largely confirmed, is not absolute [15] .…”
Section: Functions Of Ttreg and Ptregmentioning
confidence: 99%
“…Modulation in CRAMP production leads to inflammation of pancreatic islets and development of autoimmune diabetes. This was observed clearly in an animal model [16].…”
Section: Jayaswal Et Almentioning
confidence: 56%
“…Several recent studies demonstrated that gut microbiota play a pivotal role in the pathogenesis of not only gastrointestinal diseases but also systemic diseases such as diabetes mellitus, cardiovascular disease, arthritis, and obesity [7,8,9,10]. Probiotics are also well known for their usefulness in improving immune function, preventing diarrhea, and reducing blood glucose or total cholesterol levels [11,12,13].…”
Section: Introductionmentioning
confidence: 99%